Integrated STEM-based module: Relationship between students’ creative thinking and science achievement - Ahmad Adnan Mohd Shukri; Che Nidzam Che Ahmad; Norhayati Daud (University of Muhammadiyah Malang, 2020)
STEM-based learning innovations have been massively developed especially related to 21st Century skills. This study was done to explore a relationship between creative thinking and science achievement through the implementation of integrated STEM-based module on Reproduction topic. A quasi-experimental study involved pretest-posttest non-equivalent group design with sample of 60 eighth graders from a boarding school in Baling, Kedah, Malaysia. The samples was divided into two groups - 30 students of treatment group and 30 students of control group. The data were collected from pre-post-Reproduction Test Questions (RTQ) scores and pre-post-Creative Thinking Test Questions (CTTQ) scores. Pearson Correlation and one-way ANOVA at a significance level p < .05 were performed in analysing data. Findings reveal no statistically significant relationship between creative thinking and science achievement for both treatment group (r = .220, p = .243) and control group (r = .308, p = .098). Besides, there is a statistically significant and moderate and positive relationship between creative thinking indicator of fluency and science achievement (r = .463, p = .010) of the treatment group. In conclusion, general finding is an evidence that between creative thinking and science achievement shows a consistency in whatever teaching strategy implemented. In which, educators need to realize that academic achievement does not necessarily be a necessity in shaping one’s creativity. Therefore, further study is needed to investigate the relationship between these variables in the execution of STEM teaching and learning so that the findings can be generalized to a larger population.